Effectiveness of ozone therapy in the treatment of periodontal diseases: a systematic review - Pamella Valente PALMA; Rafaela de Oliveira CUNHA; Isabel Cristina Gonçalves LEITE (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT The aim of this study was to evaluate the effectiveness of ozone as an adjuvant factor in the treatment of periodontal diseases. A systematic review was carried out using the PubMed, LILACS/BIREME, CoChrane, and Scielo databases and manual searches. Clinical studies published in English, Spanish, Portuguese, and French, between 1950 and 2020 that evaluated the effects of ozone in the treatment of periodontal diseases were included. The search resulted in 178 articles, of which 24 met the proposed eligibility criteria and were selected for this review. The risk of bias was assessed for each selected study in accordance with the Cochrane risk-of-bias tool - version 5.1.0. The selected studies evaluated the effect of ozone therapy on periodontitis, gingivitis, and peri-implant diseases. It was observed that the ozone in its oily form presented the best clinical results. In cases of periodontitis, it was concluded that ozone therapy in the gaseous form did not bring any additional benefit. With respect to gingivitis, ozone provided faster remission compared to the control group. And in peri-implant disease cases, ozone had the capacity to reduce the development of mucositis. Regarding microbiology, it was observed that ozone can continuously and significantly reduce periodontal microorganisms; however, with no difference from control groups. Further studies with adequate control of biases are suggested, using ozone in the oily or aqueous form, which are the most promising forms, also evaluating the possible effectiveness of ozone by-products.